GENDER DISCRIMINATION ON THE MAIN CHARACTER FIRDAUS IN THE NOVEL “WOMAN AT POINT ZERO” BY NAWAL EL SAADAWI - Rismawati, Bau; Sunra, La (Journal of English Literature and Linguistic Studies, 2024)
Women have long suffered because of gender discrimination. In patriarchal societies, discrimination is more fatal due to its homogeneous beliefs and values. This discrimination against women often leads to mental problems for some individuals. Literature serves as a fitting platform to voice social issues, including gender-based discrimination. This study aims to analyze the gender discrimination reflected in the novel "Woman at Point Zero" using Bhui & Hosang's (2018) theory of Gender discrimination and its connection to mental health. The study was conducted using a qualitative descriptive method and analyzed using a feminist approach. The study shows that gender discrimination affects almost every aspect of society, and its impact on women's mental health is significant. The experience of Firdaus, a woman living in a patriarchal society, who constantly suffers from unfair treatment, has lost her passion for life. The study concludes that Firdaus as the main character and as a woman does not want to be treated differently, unjustly, and violently. As a woman, she wants to be treated equally, supported, respected, and have the same rights in the household, workplace, education, cultural society, and even politics.